Interaction of the Cas6 riboendonuclease with CRISPR RNAs: recognition and cleavage - Wang, Ruiying (2011)
The CRISPRs (Clustered Regularly Interspaced Short Palindromic Repeats) found in prokaryotic genomes confer small RNA-mediated protection against viruses and other invaders. CRISPR loci contain iterations of a short repeat sequence alternating with small segments of varying invader-derived sequences. Distinct families of CRISPR-associated Cas proteins function to cleave within the repeat sequence of CRISPR transcripts and produce the individual invader-targeting crRNAs. Here we report the crystal structure of Pyrococcus furiosus Cas6 bound with a repeat RNA at 3.2 Å resolution. In contrast to other Cas families of endonucleases, Cas6 clasps nucleotides 2–9 of the repeat RNA using its two ferredoxin-like domains, and the enzyme-anchored 5’ end tethers the distal cleavage site of the RNA between nucleotides 22 and 23 to the predicted enzyme active site on the opposite side of the ferrodoxin-like domains. Our findings suggest a wrap-around mechanism for CRISPR RNA recognition and cleavage by Cas6 and related processing endonucleases.